Assessment of diabetic risk among non-diabetic workers of a tertiary care hospital - Kumar, Aravind K.; Dixit, Umesh R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes is a metabolic disease characterised by high blood sugar levels and is one of the major causes of premature illness and death worldwide. There is an inflation in number of people with diabetes from 108 million in 1980 to 422 million in 2014. WHO has projected that DM is going to be 7th leading cause of death in 2030. 80% of diabetics live in low and middle income countries thereby increasing burden on their economy. Among the working population due to stress and lifestyle problems the toll is climbing in terms of morbidity, mortality and costs of society. Methods: Cross sectional study was conducted in SDM College of Medical Sciences and Hospital. Sample size was 200 with class 1 and class 2 workers 100 each. Data was collected using pre-designed and pre-tested questionnaire after taking informed consent (IDRS). Data entered in Epidata v3.1 and analyzed using IBM SPSS v20. Results: Of the 200, majority 71% belonged to 36-49 years age group. Majority 67% were males and 73% had normal BMI. A high IDRS profile was found among 18.5% of study participants. Majority 68% had moderate risk profile in relation to IDRS. Conclusions: High risk score was found in 18.5% of study subjects and moderate risk score in 68% of study subjects who were non diabetic. This is the scenario among the class I and class II staff in health care industry. Intervention needed to prevent development of diabetes among the nondiabetic working population.